Investigating teachers’ attitudes towards reflection and the frequency of their reflective practices in the Saudi context - Radhi Alshammari; Oqab Alrashidi (Humanities & Social Sciences Communications)
Abstract This study aimed to explore teachers’ attitudes towards reflection and the frequency of their reflective practices. Additionally, it examined the impact of gender and teaching levels on the frequency of teachers’ reflective practices. The participants were 219 Saudi teachers from various subject disciplines, selected using random sampling. A descriptive research design was used, and data were collected using the Reflective Attitude Survey (RAS). The results showed that teachers generally have positive perceptions about the usefulness of reflective practices in teaching. They also favored various forms of reflective practices, with a higher preference for individual and theme-based reflection over group or theme-less reflection. Teachers engaged in reflective practices to a moderate extent, with digital technology being used less frequently for such practices. No significant differences were observed in the frequency of teachers’ reflective practices in relation to gender and teaching levels.